Effect of Transglutaminase on the Characteristics of Fresh Semi-Hard Goat and Cow Cheeses. - Castillo-Chaves, Viviana María (2026)
The study evaluated the effect of the enzyme transglutaminase on the physical and sensory characteristics of fresh semi-hard cheese made from bovine and goat milk, as well as their 50% mixture. The study was conducted in San José, Costa Rica, during the year 2024. To instrumentally establish milk quality, a standardized cheese-making process was developed, generating six treatments that considered the factors: milk matrix (bovine, goat, and blend) and enzyme use (use at 0.3 g/L of milk or no use). The pH, yield, and microbiological quality were measured as control criteria. Instrumental evaluation included texture profile analysis (hardness, elasticity, cohesiveness, chewiness) and colorimetry (CIELab for coordinates a*, b*, L*, C*, and h°). Overall sensory liking was determined using a 10 cm hybrid hedonic scale with 104 panelists. A randomized complete block design with a 3x2 factorial arrangement was employed, performing a univariate factorial analysis of variance for physical parameters. For overall liking, an unrestricted random design with six levels was applied, analyzed using Ward’s hierarchical agglomerative clustering. The effect of transglutaminase on the parameters depends on the milk matrix. The enzyme may influence acceptance among some consumers, but this effect is not generalized. Prior consumer affinity with the product and the type of milk plays a role in the sensory response. Results suggest a potential improvement in semi-hard goat cheeses with the addition of this enzyme, which should be further studied in the future.